Substrates and controlled-release fertilizations on the quality of eucalyptus cuttings - Silva, Richardson Barbosa Gomes da [UNESP]; Silva, Magali Ribeiro da [UNESP]; Simões, Danilo (Departamento de Engenharia Agrícola - UFCG, 2014)
To produce cuttings with quality, the most appropriate nutritional management strategies should be sought to reduce wastage of fertilizer, while accounting for the characteristics of each substrate. This study evaluated the effect of substrates and doses of controlled-release fertilizer on the quality of Eucalyptus grandis Hill ex Maiden x Eucalyptus urophylla S. T. Blake cuttings. The substrates consisted of several mixtures: vermiculite+carbonized rice chaff+coconut fibre (1:1:1); vermiculite+coconut fibre (1:1); and vermiculite+carbonized rice chaff (1:1). These mixtures were added to 2, 4, 6 and 8 kg of controlled-release fertilizer per cubic meter of substrate. The substrates that do not support root development and have lower water retention, independently of the dose of controlled-release fertilizer, reduce the quality of the root system. For substrates with proper values of water retention, such as vermiculite+coconut fibre (1:1) and vermiculite+carbonised rice chaff+coconut fibre (1:1:1), the utilization of dose 2 kg of controlled-release fertilizer to each cubic meter is enough to promote cuttings with greater quality of the root systems and proper heights and stem diameters.

Deve-se buscar, para produzir mudas de qualidade, manejos nutricionais mais adequados que reduzam o desperdício de fertilizantes considerando as características de cada substrato. Este estudo avaliou o efeito de substratos e doses de fertilizante de liberação controlada na qualidade de mudas clonais de Eucalyptus grandis Hill ex Maiden x Eucalyptus urophylla S. T. Blake. Os substratos se constituíram das seguintes misturas: vermiculita+casca de arroz carbonizada+fibra de coco (1:1:1); vermiculita+fibra de coco (1:1) e vermiculita+casca de arroz carbonizada (1:1). A essas misturas foram adicionados 2, 4, 6 e 8 kg de fertilizante de liberação controlada por metro cúbico do substrato. Os substratos que não dão suporte ao crescimento das raízes e possuem baixa retenção de água, independente da dose de fertilizante de liberação controlada, reduzem a qualidade do sistema radicular. Para substratos com capacidade adequada de retenção de água, como os constituídos por vermiculita+fibra de coco (1:1) e vermiculita+casca de arroz carbonizada+fibra de coco (1:1:1) a dose 2 kg de fertilizante de liberação controlada por metro cúbico é suficiente para formar mudas com alturas da parte aérea e diâmetros do colo adequados e sistema radicular de qualidade.
Substratos e fertilizações de liberação controlada na qualidade de mudas clonais de eucalipto
Keywords: nutrientes; fertilizante; sistema radicular; retenção de água; viveiro florestal; nutrients; fertilizer; root system; water retention; forest nursery